Distinction of HPV-type viruses in Penaeus chinensis and Macrobrachium rosenbergii using a DNA probe - Lightner, D. V.; Redman, R. M.; Poulos, B. T.; Mari, J. L.; Bonomi, J. R.; Mohamed Din, Mohamed Shariff (Asian Fisheries Society, 1994)
Histological sections of hepatopancreas tissue from postlarval Macrobrachium rosenbergii from Malaysia infected with an HPV- type (HPV-Mac) virus were tested for possible virus homology with a DNA probe developed from an HPV-type virus (HPV-Chin) of Penaeus chinensis from Korea. No reaction of the HPV-Chin probe was observed with HPV-Mac intranuclear inclusion bodies or infected cells. These findings, along with distinctive cytopathological differences between cells infected with HPV-Chin and HPV-Mac, indicate that these are distinctly different viruses within the parvovirus family.